Comparison of Reproductive Performance of Brahman Crossbred Females with other Available Cattle Genotypes in Mymensingh District (Journal of the Bangladesh Agricultural University, 2024)
The study was conducted to evaluate the reproductive performance of Brahman crossbred females and compare them with other available cattle genotypes found in Mymensingh district. Reproductive performance data on 35 Brahman crossbreds, 32 Indigenous, 12 Sahiwal crossbreds and 21 Friesian crossbreds were collected from three different villages (Baera, Bhabkhali and Dowhakhola) adjacent to Bangladesh Agricultural University, Mymensingh. Statistical analyses were performed using Statistical Analysis System (SAS) computer program. Reproductive performance of Brahman crossbred was recorded as age at first service: 32.29 ± 1.46 months, age at first calving: 42.00 ± 1.49 months, service per conception: 1.7 ± 0.17, overall conception rate: 0.76 ± 0.05 (76.11%), conception at first service: 0.63 ± 0.08 (62.85%) and gestation length: 282.97 ± 0.78 days. Highly significant (p